A RESEARCH STUDY OF FORTS AND CAVES IN RAIGAD DISTRICT WITH ARCHITECTURAL PERSPECTIVE (International Journal of Food and Nutritional Sciences, 2023)
Foreign records regarding Konkan can be found. Dr. Daud Dalvi, Dr. Jamkhedkar, P.K. Ghanekar, Vidya Dehjiya, Dr. Dhavalikar, Dr. Prabhakar Dev have studied the architectures but architectures of Raigad region have not been studied specially. Architectures include forts, caves. The presented research project will be useful to the society, historical scholar, Gri Premi and college students. Exploring them as architectures, forts, caves. The role behind this research is to promote historical work. Maximum forts and caves in Raigad District have been ignored due to lack of amenities like water management, residential, transportation, security, electricity.